(untitled) (Conference Zone, 2021)
This article discusses the topical problem of tolerance, its levels. Considerable attention is paid to teaching the English language as a means of tolerance development among university students. The authors focus on teaching foreign language communication in the context of the dialogue of cultures, involving the interrelated solution of communicative, educational and developmental tasks. The principle of education in the context of the dialogue of cultures creates conditions for the research of the cultures of the countries of the studied language based on the world culture and the national culture rethinking through its lenses, the result of which is mutual understanding.